EVALUASI KINERJA DINAS PEKERJAAN UMUM DAN PENATAAN RUANG KABUPATEN ROKAN HILIR DALAM MENGATASI ABRASI DI KAWASAN SUNGAI ROKAN (STUDI KASUS DI KELURAHAN RIMBA MELINTANG) - Hermawan Hermawan; Moris Adidi Yogia (PUBLIKA : Jurnal Ilmu Administrasi Publik, 2018)
Abrasion is one of the problems that threaten coastal conditions that can also threaten the river line so that backward causing the land eroded and the river increasingly widespread, of course this is very dangerous for people, especially for those who live on the riverbank because the consequences of this abrasi make the loss of land agricultural, community gardens, community houses and public roads if this continues to happen, this should be the government’s concern. the purpose of this study is to know and explain how the Performance of Public Works and Spatial Planning of Rokan Hilir in Overcoming Abrasion in the Rokan River Area (Case Study in Kelurahan Rimba Melintang), as well as to know and explain the obstackles that experienced by the of Public Works and Spatial Planning of Rokan Hilir in Overcoming Abrasion In the Rokan River Area (Case Study in Kelurahan Rimba Melintang). To know the Performance of Public Works and Spatial Planning of Rokan Hilir in Overcoming Abrasion in the Rokan River Area (Case Study in Kelurahan Rimba Melintang), the researcher took the population and the sampel amounted to 43 people, namely 3 employees of public works and spatial planning agency and 40 people which affected by the Abrasion in Kelurahan Rimba Melintang, while the key informant in this research is the Head of Public Works and Spatial Planning. The sampling technique for public Service Officer and Urban Spatial Planning of Rimba Melintang Urban Village is Incidental sampling. While the theory of evaluation that researchers use is William N.Dunn theorist where the criteria of evaluation criteria is Effectivenees, Efficiency, Adequacy, Flattening, Responsiveness and Accuracy. After all data is analyzed by qualitative and quantitative method hence the Performance of Public Works and Spatial Planning of Rokan Hilir in Overcoming Abrasion in the Rokan River Area (Case Study in Kelurahan Rimba Melintang),is “ Less Good” therefore for the future to overcome the abrasion of the rokan river area needs to be improved again.